A mineralogical investigation into the pre-concentration of the Nechalacho deposit by gravity separation. (1st June 2018) - Marion, C.; Grammatikopoulos, T.; Rudinsky, S.; Langlois, R.; Williams, H.; Chu, P.; Awais, M.; Gauvin, R.; Rowson, N.A.; Waters, K.E.
Highlights: QEMSCAN is used to characterize the Nechalacho deposit for gravity separation. Liberation characteristics suggest opportunities to concentrate unliberated minerals. DMS results were accurately predicted by QEMSCAN gravity modeling of the feed. A spiral and Knelson Concentrator successfully concentrate valuable minerals. Abstract: The Nechalacho rare earth element (REE) deposit is located in the Northwest Territories, Canada. Of the various REE-bearing minerals in the deposit, zircon is significant due to its elevated heavy rare earth element (HREE) content. Most studies performed on this ore to date have focused on fully liberating REE-bearing minerals through fine grinding prior to a separation stage. However, previous lab scale work has shown that zircon can be concentrated in relatively coarse sizes, suggesting the potential to pre-concentrate the ore by gravity separation without complete liberation. The current work investigates the pre-concentration of the Nechalacho deposit using a spiral concentrator and a Knelson Concentrator on a relatively coarse (d80 = 97 μm) feed. The feed sample and the resultant fractions, produced by each separation technique, were analyzed with ICP-MS to determine the zirconium and REE content. The samples were also analyzed with QEMSCAN to identify the effect of particle size, mineral liberation and association characteristics, and mineral particle SG distributions for each gravity separation technique. The results suggest that the value minerals can be effectively concentrated by gravity separation even when they are poorly liberated. It is important to note that the process examined here is not representative of the currently selected process design or recovery for the Nechalacho deposit. Any application of this process to this deposit would require optimization to ensure appropriate grade and recovery targets are met.